Case Report: A rare pediatric case of hepatitis B virus infection with acute disseminated encephalomyelitis/Guillain–Barré syndrome spectrum diseases - Li, Yingxue; Hu, Dongxu; Shen, Xing; Mao, Xiaoyan (Frontiers in Pediatrics, 2026)
A 12-year-old girl with convulsions was incidentally found to be infected with hepatitis B virus(HBV), with HBVdeoxyribonucleic acid (DNA) and HBsAg positivity in the cerebrospinal fluid. The patient experienced frequent convulsions and consciousness disorders, and positive anti-GQ1b/anti-GD1b antibodies were detected in the cerebrospinal fluid. Acute disseminated encephalomyelitis(ADEM)/Guillain–Barré syndrome (GBS) spectrum disorders were observed on brain and spinal cord magnetic resonance imaging, indicating a high likelihood of HBV-related ADEM+/GBS spectrum disorders. After treatment with intravenous hormone, immunoglobulin, antiviral therapy using entecavir, and antiepileptic medication, the neurological damage completely resolved, the hepatitis B viral load decreased significantly, and liver function returned to normal. ADEM+/GBS spectrum diseases are immune-mediated disorders of the central nervous system that occur after viral infection. However, the potential relationship between hepatitis B virus infection and ADEM+/GBS spectrum diseases remains an area of ongoing investigation. In this case, the combination of hormones and intravenous immunoglobulin did not affect the anti-HBV effect of entecavir, and the patient fully recovered from the neurological damage within three months of disease onset. This case highlights hepatitis B-related neurological diseases and encourages further sharing of clinical experiences.